R-cell: a module for a self-reconfigurable robotic system - Chatzigeorgiou, Dimitris M.; Kyriakopoulos, Kostas J.; Loizou, Savvas (My University, 2008)
In this paper, we introduce the concept of a novel robotic module, the "R-Cell". R-Cell can be utilized in constructing distributed, homogeneous robotic systems. Each R-Cell is a rectangle endowed with: (a) motion capabilities provided by four revolutionary joints, each equipped with a clamping mechanism, and (b) deformation capabilities realized by four prismatic joints. The proposed module provides the resulting modular robotic structures with dexterous deformation and force creating capabilities. The resulting robotic structures are not defacto rigid, but can change shape & form even without any cell-reconfiguration. Our concept could be useful for a great variety of applications encompassing modular robotics like self-assembly, self-repair and reactive shape optimization just to mention a few, that conventional robots cannot accommodate.
Keywords: Actuators; Equations; Strontium; Mobile robots